Great Novels of E.M. Forster : Where Angels Fear to Tread : The Longest Journey : A Room With a View : Howards End - Forster, E. M. (Edward Morgan), 1879-1970; Introduction by Auchincloss, Louis (New York Skyhorse Publishing, 2014)
A renaissance of E.M. Forster is certainly under way. The success of the many films based upon his novels demonstrates Forster's appeal to the modern audience and his aptitude for entertaining a mass quantity of readers over several decades. Four of his best novels are brought together here in one volume:Where Angels Fear to TreadThe Longest JourneyA Room with a ViewHowards End"E. M. Forster's characters are the most lifelike we have had since Jane Austen laid down the pen." Virgina Woolf"[Forster] does not hesitate to kill off a character right after introducing him with a careful description which leads us to anticipate a larger role." Louis Auchincloss"The shapeliness of his prose and his plotting still satisfies. The width remains piercing and seamlessly painless." the New York Times"There is no questioning or resisting the charm of Mr. Forster. The Longest Journey steadily attains beauty." Saturday Review
Keywords: English fiction -- Inheritance and succession -- Manners and customs